Origins of strigolactone and karrikin signaling in plants - Wang, Q.; Smith, S. M.; Huang, J.
Strigolactones (SLs)and karrikins (KARs)are butenolides that influence multiple aspects of plant growth and development. D14 and KAI2 are members of the ?/?-fold hydrolase superfamily and act as receptors of SLs and KARs, as well as of unidentified endogenous KAI2-ligands (KLs). Phylogenetic analyses suggest that plant KAI2 was derived from bacterial RsbQ via horizontal gene transfer (HGT)before the emergence of streptophytes. The D14/KAI2 and RsbQ proteins share conserved tertiary structures and functional features. In this opinion article, we suggest that the acquisition of RsbQ by plant cells was fundamental to the formation of butenolide sensing systems. Recruitment of additional signal transduction components and gene duplication subsequently led to versatile butenolide signaling systems throughout land plants.
Keywords: PHYTOHORMONE; HORIZONTAL GENE TRANSFER; PLANT-MICROBE INTERACTION; PLANT EVOLUTION